LABOR GYMNASTICS AS A MEAN OF PROMOTING THE QUALITY OF LIFE OF WORKERS (Fiep Bulletin - online, 2017)
Currently, in Brazil, the issues related to the economic adequacy of work environments are still far from being a reality.The competitiveness of professionals in the labor market, the fierce competition of companies, the pursuit for increasedproductivity and the increasing demands of consumers form the perfect set to expose individuals to high levels of tension andstress, compromising the quality of life and the health of the workers. Therefore, programs designed for promoting health andimproving the quality of life of employees have become indispensable and must integrate the culture of companies. Quality of lifeis not only related to aspects such as physical, functional, emotional or mental well-being, but also the sum of other factorsinherent to work, such as living with friends and other life circumstances, especially their relatives. Therefore, this article seeksreflections on the importance of the practice of planned physical activity within the work environment, known as LaborGymnastics. Studies demonstrate the importance of the Labor Gymnastics in the prevention of occupational diseases, such asR.S.I and O.W.R.D., the reduction of work accidents and the incidence of absences, as well as the increase of productivity, thereduction of medical expenses and, consequently, higher financial return for companies.
Keywords: Occupational Gymnastics; Quality of Life; Workers